2011
DOI: 10.3174/ajnr.a2397
|View full text |Cite
|
Sign up to set email alerts
|

Pseudoprogression and Pseudoresponse: Imaging Challenges in the Assessment of Posttreatment Glioma

Abstract: SUMMARY:The current standard of care for newly diagnosed cases of high-grade glioma is surgical resection followed by RT with concurrent chemotherapy. The most widely used criteria for assessing treatment response are based on a 2D measurement of the enhancing area on MR imaging known as the Macdonald Criteria. Recently, nontumoral increases (pseudoprogression) and decreases (pseudoresponse) in enhancement have been found, and these can confuse outcome evaluation. Here we review pseudoprogression and pseudores… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
289
0
6

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 471 publications
(313 citation statements)
references
References 34 publications
3
289
0
6
Order By: Relevance
“…We believe it is more important not to overlook the diagnosis of late PsP as it reflects an ongoing benefit from previous/current treatment. Hence, in the event of a TBR max value in between 1.0 and 2.4 it might be safest (when trying to avoid missing PsP) to defer the initiation of a salvage treatment until a follow-up MRI has been performed or to obtain a tumor specimen via biopsy to confirm Patients with MGMT-methylated glioma are more likely to develop PsP, amounting to an incidence of up to 31% as compared with 5% in patients with non-methylated tumors (8,16,21). Accordingly, our study found that almost all patients with late PsP had a methylated MGMT promoter.…”
Section: Discussionmentioning
confidence: 99%
“…We believe it is more important not to overlook the diagnosis of late PsP as it reflects an ongoing benefit from previous/current treatment. Hence, in the event of a TBR max value in between 1.0 and 2.4 it might be safest (when trying to avoid missing PsP) to defer the initiation of a salvage treatment until a follow-up MRI has been performed or to obtain a tumor specimen via biopsy to confirm Patients with MGMT-methylated glioma are more likely to develop PsP, amounting to an incidence of up to 31% as compared with 5% in patients with non-methylated tumors (8,16,21). Accordingly, our study found that almost all patients with late PsP had a methylated MGMT promoter.…”
Section: Discussionmentioning
confidence: 99%
“…Contrast enhancement in brain tumors post-treatment is nonspecific and may not always be indicative of tumor response. Both pseudoprogression, an increase in the non-tumoral enhancing area, and pseudoresponse, a decrease in the enhancing area, show that enhancement alone is not a reliable measure of tumor activity but rather reflects a disturbed bloodbrain barrier [4,9].…”
Section: Discussionmentioning
confidence: 99%
“…Pseudoprogression is an early-to-subacute post-treatment effect observed on the imaging of high-grade gliomas usually occurring within the initial three months following the start of chemoradiation therapy [2][3][4][5][6]. The increased gadolinium contrast enhancement on magnetic resonance imaging (MRI) can be misinterpreted as tumor recurrence or radiation necrosis (RN).…”
Section: Introductionmentioning
confidence: 99%
“…We thus may underestimate the strength of the evidence. Reviews with such partial responses included: "was the search strategy comprehensive", (DTI-mTBI, n 5 [45][46][47][48]52,53,55,57,63,64,66 ), "are all of the results presented with confidence intervals", (DTI-mTBI n 5 1; 34 DSCglioma n 5 4 50-52,65 ), "does it state the study design of all included articles" (DTI-mTBI, n 5 3; 25,39,44 DSC-glioma, n 5 3 62,64 ) and "does it specify the number of subjects for all included studies" (DTI-mTBI, n 5 11; 8,25,27,28,31,34,37,38,40,42,44 DSC-glioma, n 5 8 47,50,51,57,60,61,63,64 ).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding critical appraisal worksheet grades for DTI-mTBI detection reviews, 1 review achieved Grade A, 29 8 reviews achieved Grade B 8,24,25,36,39,41,42,44 and 14 reviews achieved Grade C. 6,[26][27][28][30][31][32][33][34][35]37,38,40,43 Of the reviews of DTI-mTBI outcome prediction, three reviews achieved Grade B 25,39,41 and the remaining reviews were Grade C. 6,[26][27][28][30][31][32]37,40 Of the reviews of DSC-glioma detection, 1 review achieved Grade A, 7 1 review achieved Grade B 62 and 24 reviews achieved Grade C. 9,12,[45][46][47][48][49][50][51][52][53][54]…”
Section: Classification and Grading Of Individual Review's Overall Qumentioning
confidence: 99%